Language Processing Evidence for Linguistic Structure - Felser, Claudia (IBERIA: An International Journal of Theoretical Linguistics, 2014)
This article illustrates how data from language processing experiments might bear on theoretical linguistic issues and controversies. Based on the results from real-time processing studies of subject raising vs. subject control structures and successive-cyclic wh-movement in English, and of long-distance scrambling in Japanese, this article examines how language processing data can help shed light on the nature of the linguistic representations of different types of non-canonically ordered sentences.